An Analysis of Impoliteness Strategies Used by Wednesday Addams in Netflix’s Wednesday Season 1 - Novera, Tria; Amalia, Yuni Sari (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
In today’s society, impoliteness in communication has become increasingly normalized, especially in media. This study analyzes the types, functions, and contextual factors of impoliteness strategies used by Wednesday Addams, the main character in the Netflix series Wednesday Season 1. Employing Culpeper’s (2011) impoliteness theory and a qualitative descriptive method, data were collected from selected dialogues that feature impolite language. The findings reveal that Wednesday uses all five impoliteness strategies such as bald on record, positive impoliteness, negative impoliteness, off-record, and withhold politeness with positive impoliteness being the most frequent. Positive impoliteness emerges as the most frequently used strategy, as Wednesday often targets other’s positive face to express her emotional detachment. These strategies serve primarily affective functions, expressing emotions such as irritation or detachment. The study also finds that Wednesday’s impoliteness is influenced by contextual factors, particularly social norms, power relations, and situational context.